Antepartum and Intrapartum Risk Score to Recognize Birth Asphyxia After Delivery - Kitiyodom, Siraya (Srinagarind Medical Journal, 2023)
Background and objective: Birth asphyxia is the main factor for fatality in neonatal. The evaluation of the risk factors and the prediction of birth asphyxia during the antepartum and intrapartum periods could potentially reduce the rate of the incidence. This evaluation aimed to study the characteristics of the risk factors and to create the risk scoring system targeting birth asphyxia from the risk factors identified during antepartum and intrapartum. Materials and methods: The study was a case-control prognostic prediction research. The data was collected retrospectively from the electronic medical record and the delivery summary at Maharat Nakhon Ratchasima hospital’s labor room from January 1st 2018 - December 31st, 2019. The inclusion criteria of the participants include the patients who delivered at 28 weeks gestation and birth weight was greater than or equal to 1,000 grams, with no significant birth defects or death. The subjects were separated into: (1) the mother who gave birth with birth asphyxia (case; apgar score ≤7) 300 subjects, and (2) the mother who gave birth without birth asphyxia (control; apgar score >7) 1,279 subjects. The data was analyzed with multivariable logistic regression and the coefficient was calculated into the clinical risk score. Results: The factors to predict birth asphyxia were gestational age, antenatal care, gestational diabetes mellitus, severe preeclampsia, antepartum hemorrhage, multifetal pregnancy, the fetus in positions other than head-first, meconium strain, polyhydramnios, oligohydramnios and nonreassuring NST. Results showed that the area under the curve (AuROC) was 82.2% (95% CI;79.1, 85.4). The clinical risk scores were categorized according to the likelihood ratio of positive (LHR+) for birth asphyxia. In the low-risk group (risk score < 3.5), LHR+ for birth asphyxia was 0.27 (95%CI; 0.02,0.37). In the moderate risk (risk score 3.5 - 13) the LHR+ was 1.37 (95% CI; 1.08,1.73), and the high-risk group (risk score > 13) showed 18.25 LHR+ (95% CI; 11.55, 29.63). Conclusion: Pregnant women with the antepartum and intrapartum risk score more than 13 have a 18.25 times higher risk of birth asphyxia. Additional care and close monitoring of this group of patients are warranted to decrease the occurrence of birth asphyxia.